PERBANDINGAN MASSA OPTIMUM CAMPURAN PEWARNA ALAMI PADA KAYU JENIS AKASIA (Acacia leucopholea) - Bogoriani, N. W.; Bawa Putra, A. A. (Jurnal Kimia (Journal of Chemistry), 2012)
Wood is one of several materials that is very useful for man. Now adays wood with low quality tends to be used more. The high demand causes good quality wood getting harder to find. To overcome this problem, low quality wood like acacia was dyed using a mixture of natural dye. The dye was prepared from urcaria gambir-piper betle Linn leaves, areca catechw seed, and 0.5 % w/v of CaCO3 in water. The physical and chemical properties of the dyed wood was tested using aluminium sulphate solution and detergent solution. The optimum mass for the dye was 5.3 uncaria : 3.0 piper; 3.0 areca. After 30 minutes soaking in the mixture, reddish brown coolour was produced, with maximum adsorption of 0.23 g in wood surface that showed durability of the dye highest from dye appearance and mixture mass that be lost.
Keywords: natural dye, reactive dye